Rethinking caravanism in Portugal: A sustainable and regenerative approach - Cecílio, D. F.; Pereira, L.; Vinhas da Silva, R.; Dias, Á. (Regenerative tourism for social development, 2025)
This research examines caravanning's potential to be a catalyst for regenerative tourism in Portugal. Using the VRIO framework, the study, through interviews with caravanners, assesses whether caravanning represents a sustainable competitive advantage. Findings show it is valuable, rare, and difficult to imitate, highlighting its potential to contribute to destination regeneration. However, achieving sustainable competitive advantage requires creating favorable conditions for caravanning, including infrastructure, policies, and planning. By investing in these areas, Portugal can leverage caravanning to promote sustainable and regenerative tourism.